Pengaruh Pendidikan Akhlak dan Pembinaan Sholat terhadap Pembentukan Karakter Eks Wanita Tuna Susila - Fitrotun Rahmawati; A. Dardiri Hasyim (Program Pascasarjana UNU Surakarta, 2023)
This study aims 1) to find out how the influence of moral education on the character formation of former prostitutes, 2). To find out how the influence of prayer coaching on the character formation of former prostitutes, 3). This study aims to determine the effect of moral education and moral development on character building for former prostitutes at the